Leadership In Ethiopian Public Universities; Capacity And Challenges - Gebremedhin, Mulugeta Fisseha; Gupta, Bhawna (Gyan Management Journal, 2023)
Literature is evidently characterized by a plethora of definitions and  correspondingly the actual practice of leadership is characterized by  complexity. This applies to the leadership of higher education too. But it  is the public universities that has to contend more with competing needs  and expectations of diverse stakeholders. This paper thus examines  leadership capacity and challenges in Ethiopian public universities. To  this end a mixed approach was utilized. The result shows that leaders of  the study area lacks the ability to manage complexity and change, and  a knowledge of the technical and quantitative skills necessary , and the  managing of diversity, the ability to work as a team were also lacking.  Furthermore, Leaders have a propensity to concentrate on known issues  and known solutions. The Study also suggested that leaders with a full  range of traits on personal, organizational, performance and social  mastery are needed to lead and fully engage in the process of achieving  sustainable performance outcomes. Empowerment must play a role in  developing ‘the best qualities’ of our people. Finally, providing a training  link between all levels of the hierarchy were deemed vital for leadership  excellence to flourish
Keywords: Taxation; Cryptocurrency; Crypto assets; Virtual Digital Assets